Changes in traumatic mechanisms of injury in Southern California related to COVID-19: Penetrating trauma as a second pandemic. Issue 4 (30th April 2021) - Yeates, Eric O.; Grigorian, Areg; Barrios, Cristobal; Schellenberg, Morgan; Owattanapanich, Natthida; Barmparas, Galinos; Margulies, Daniel; Juillard, Catherine; Garber, Kent; Cryer, Henry; Tillou, Areti; Burruss, Sigrid; et al.
Abstract : BACKGROUND: The COVID-19 pandemic resulted in a statewide stay-at-home (SAH) order in California beginning March 19, 2020, forcing large-scale behavioral changes and taking an emotional and economic toll. The effects of SAH orders on the trauma population remain unknown. We hypothesized an increase in rates of penetrating trauma, gunshot wounds, suicide attempts, and domestic violence in the Southern California trauma population after the SAH order. METHODS: A multicenter retrospective analysis of all trauma patients presenting to 11 American College of Surgeons levels I and II trauma centers spanning seven counties in California was performed. Demographic data, injury characteristics, clinical data, and outcomes were collected. Patients were divided into three groups based on injury date: before SAH from January 1, 2020, to March 18, 2020 (PRE), after SAH from March 19, 2020, to June 30, 2020 (POST), and a historical control from March 19, 2019, to June 30, 2019 (CONTROL). POST was compared with both PRE and CONTROL in two separate analyses. RESULTS: Across all periods, 20, 448 trauma patients were identified (CONTROL, 7, 707; PRE, 6, 022; POST, 6, 719). POST had a significantly increased rate of penetrating trauma (13.0% vs. 10.3%, p < 0.001 and 13.0% vs. 9.9%, p < 0.001) and gunshot wounds (4.5% vs. 2.4%, p = 0.002 and 4.5% vs. 3.7%, p = 0.025) compared with PRE and CONTROL, respectively. POST had a suicide attempt rate of 1.9% and a domestic violence rate of 0.7%, which were similar to PRE ( p = 0.478, p = 0.514) and CONTROL ( p = 0.160, p = 0.618). CONCLUSION: This multicenter Southern California study demonstrated an increased rate of penetrating trauma and gunshot wounds after the COVID-19 SAH orders but no difference in attempted suicide or domestic violence rates. These findings may provide useful information regarding resource utilization and a target for societal intervention during the current or future pandemic(s). LEVEL OF EVIDENCE: Epidemiological, level IV.